Development and effectiveness analysis of a safety management model for SMEs integrating lean management innovation with SQCDP framework. - Yichen Yin; Xinyi Ouyang; Jinggang Zhang; Haoyu Chen; Haochen Xu; Wanting Zhang; Chongqin Lin; Zulin Zhou (PLoS ONE)
This study organically integrates the safety, quality, cost, delivery, and people (SQCDP) management mode and lean management to create the SQCDP + lean safety management (SLSM) mode, which addresses certain problems faced by China's small- and medium-sized enterprises (SMEs), such as imperfect safety management systems, poor regulatory implementation, challenging problem correction, and perfunctory management. It then explains the benefits proposed mode for SMEs and the establishment of a novel mode that aligns with the current safety production and operation management of SMEs. The application of the SLSM mode to a private machinery manufacturing company in Wenzhou resulted in the effective shouldering of safety responsibilities by the company, a year-on-year decrease in accident rates, and a significant increase in production efficiency, thereby providing corporate managers with guidance and suggestions for making improvements.